TESTICULAR AND EPIDIDYMIS TUBERCULOSIS IN BUFFALOES MANAGED EXTENSIVELY IN AMAPA STATE, BRAZIL - H.F.L.Ribeiro; S.T. Rolim Filho; E.M; Barbosa; R.N; Pereira; N. S; Picanço; K.B. Nunes; W.G.Vale; W.L.A. Pereira S (Journal of Animal and Plant Sciences, 2012)
This study was carried out in five farms in the state of Amapa, in Amazon region, Brazil, where buffalo and cattle are commonly managed extensively without appropriate programs of sanitary prevention. 123 andrological examinations were analyzed from 2006 to 2008, which had been performed in mixed Murrah and Mediterranean males aged 2 to 10 years (average age was 4.8 years). Data were based on the Breeding Soundness Examination (BSE) which in their turn was based on inspection and palpation of scrotum, testicles and epididymis; rectal palpation of glands, prostate, ampoules and duct deferents. Affected testicles and epididymis were removed, dissected, analyzed, photographed and kept in a solution with 10% formaldehyde and then transported to the laboratory where they were processed and stained by HE. In 19 (15.4%) of 123 buffaloes showed alterations in testicles and/or epididymis. Inspection and palpation showed lobulated, asymmetrical testicles with no mobility, the consistency of which ranged from flaccid to fibrosis. Histopathological analyses in those 19 animals showed that 10 of them (52.6%) had tuberculosis. 12 animals out of 19 (63,1%) revealed left-sided alterations in 5 buffaloes (26.3%) and in 2 (10.5%) alterations affected both testicles and epididymis. Among the 19 animals that had alterations, 15 (78.9%) had their epididymis also affected, specially their tails. The tails had a big volume, very protruding and always had fibrous consistency. The volume of affected testicles and epididymis was 20 to 30% larger than normal.
Keywords: Amazon; Brazil; buffaloes; epididymis; testis; tuberculosis